6π-Electrocyclization in water: microwave-assisted synthesis of polyheterocyclic-fused quinoline-2-thiones. Issue 14 (1st July 2020) - Li, Xiao-Yun; Liu, Yan; Chen, Xiao-Lan; Lu, Xin-Yuan; Liang, Xing-Xing; Zhu, Shan-Shan; Wei, Chuan-Wan; Qu, Ling-Bo; Yu, Bing
Abstract : Microwave-assisted synthesis of polyheterocyclic-fused quinoline-2-thiones through the annulation of ortho -heteroaryl anilines and CS2 was realized in water without using any catalysts and additives. Abstract : Microwave-assisted synthesis of polyheterocyclic-fused quinoline-2-thiones through the annulation of ortho -heteroaryl anilines and CS2 was realized in water without using any catalysts and additives. The desired products were obtained in high yields through simple filtration. A remarkable E -factor of 0.45 and an EcoScale score of 85.5 were obtained.